Biomechanical Analysis of Drag Push Movements in Indoor Hockey - Muhamad Farhan Pratama; Agus Rusdiana; Tian Kurniawan; Iwa Ikhwan Hidayat (Universitas Negeri Semarang, 2025)
The study was an attempt to analyse the biomechanical aspects of drag push movements in professional and amateur indoor hockey players. This study was a cross-sectional assay in which a sample of 10 (five professional and five amateur) athletes were included. Analysis were concentrating on several kinematic variables including ball speed, foot support width, distance between the ball and front foot, drag trajectory length, drag phase duration and average drag velocity. A high-speed camera, Kinovea motion analysis software and speed gun were used to collect data. Results from the analysis revealed that two primary variables were significantly different between groups, the drag time differed significantly: 0.30 seconds for the professional group and 0.42 seconds for the amateur group (p = 0.046). Strange enough, average drag speed was even elevated to 1.68 m/s in amateur athletes (vs a value of 1.30 m/s in professionals), though being not significant (p = 0.839) and also not translated into increased ball speed gained with each OF shot, and drag distance (p = 0.005). The ball speed swung by professional and amateur players was virtually higher in the former, but it did not reach a statistical significance. These results support the knowledge that drag push power depends on the capacity of efficiently linking the coordination to optimize drag trajectory. According to these findings, the current study recommends that training programs for amateur hockey players should pay more attention on enhancing dynamic skills for better drag push performance in indoor-hockey.